ANTENATAL HEALTH CARE PROVISION AND MATERNAL HEALTH IN MALABA HEALTH CENTRE IV IN MALABA TOWN COUNCIL, TORORO DISTRICT - EMEJE J_BSWASA_2024.pdf (My University, 2024)
The study aimed to assess the effect of antenatal health care provision on maternal health at Malaba Health Centre IV in Malaba Town Council, Tororo District, with a focus on three specific objectives: assessing the quality of antenatal care services, evaluating the accessibility of antenatal health services, and examining the effectiveness of health education and counseling on maternal health. Utilizing a cross-sectional survey design and a sample of 40 respondents from a population of 45, selected using Morgan’s sampling technique, the findings revealed varied results. For the first objective, the quality of antenatal care services was generally viewed positively, with significant satisfaction reported. However, regression analysis indicated a minimal relationship between antenatal care quality and maternal health, with an R-squared value of 0.009, suggesting that only 0.9% of the variability in maternal health outcomes could be explained by the quality of care. For the second objective, while accessibility aspects were largely viewed positively, regression results showed a weak relationship between accessibility and maternal health, with an R-squared value of 0.030, indicating that only 3% of the variability in maternal health was explained by accessibility. Lastly, regarding the effectiveness of health education and counseling, although these services were generally well-regarded, the regression analysis demonstrated that the effectiveness of counseling had a limited impact on maternal health, with findings suggesting that further improvements were needed. Based on these findings, the study concluded that while antenatal care services at Malaba Health Centre IV were positively perceived, there were significant gaps in quality, accessibility, and educational effectiveness that impacted maternal health. The study recommended that efforts be made to address these gaps by improving communication, expanding access to services, and enhancing the relevance and clarity of health education and counseling.